2023
DOI: 10.1108/jima-06-2021-0179
|View full text |Cite
|
Sign up to set email alerts
|

Effects of religiosity, halal knowledge and halal certification on the intention of Muslims to use the halal vaccine during Covid-19 pandemic

Abstract: Purpose This study aims to analyze the effect of religiosity (RE), halal knowledge (HK) and halal certification (HC), attitudes, subjective norms and vaccine quality on the Muslim community’s intention to use halal vaccines in Indonesia. Design/methodology/approach This study involved 725 Muslim respondents in 32 Indonesian provinces. The model used was based on the theory of reasoned action development with the partial least squares structural equation modeling as the data processing tool. Findings The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 78 publications
0
0
0
Order By: Relevance
“…This indicated that the people of Melaka Tengah believed that religion encourages them to take COVID-19 vaccines. In comparison, a recent survey conducted by Faturohman et al (2021) and Sudarsono et al (2023) showed that perceived religiosity did not affect the intention of COVID-19 vaccination among Indonesians.…”
Section: Regression Analysis On the Relationship Between Perceived Re...mentioning
confidence: 59%
See 2 more Smart Citations
“…This indicated that the people of Melaka Tengah believed that religion encourages them to take COVID-19 vaccines. In comparison, a recent survey conducted by Faturohman et al (2021) and Sudarsono et al (2023) showed that perceived religiosity did not affect the intention of COVID-19 vaccination among Indonesians.…”
Section: Regression Analysis On the Relationship Between Perceived Re...mentioning
confidence: 59%
“…For Muslim respondents, each time a discussion on the topic of COVID-19 vaccination was brought up, the subject of its unlawful halal status was certainly brought up as well (Abdul Aziz et al, 2021). In Indonesia, due to the limited dose availability and difficulty of selection, the Indonesian Council of Ulama allowed the use of AstraZeneca in emergency situations, although these vaccine types had used pig trypsin during AstraZeneca's manufacturing (Sudarsono et al, 2023). Most respondents strongly agreed with the statement in the instruments, as illustrated in Table 4.0, that religion is their guidance in life, 3.55 (SD =.83), and religion influences their life decisions, 3.30 (SD =.93).…”
Section: Regression Analysis On the Relationship Between Perceived Re...mentioning
confidence: 99%
See 1 more Smart Citation
“…Halal labeling includes halal writing or statements on product packaging to show that the product in question has the status of halal product (Hidayatullah, 2020;Sudarsono et al, 2023). Kotler (2002) states that beliefs and attitudes can influence purchasing behavior (Kotler, 2002).…”
Section: Halal Labeling and Purchase Lemonilo Instant Noodlesmentioning
confidence: 99%